Theoretical and Experimental Antiscaling Performance Study of Several Inhibitors to Prevent Barium Sulfate Formation during Water Injection in Oil Reservoirs. (20th January 2023) - Li, Haitao; Li, Ran
Abstract : One of the hazards from mineral precipitation during oilfield production is scaling, which mainly manifests in the following three aspects: it leads to reduction in permeability, in deliverability, and in water intake capacity of reservoir; the flowing area of pipeline shrinks, which could elevate the fluid flow resistance and even lead to well shut; and scaling could also contribute to pressure loss and may cause tube blasting when it is serious. Therefore, scaling not only improves production costs but also poses a serious threat to production safety. The injection of scale inhibitors in the process of water flooding is the main method to combat scale build-up. Efficiency of inhibitor or adsorption between inhibitor and scale is the key factor that determines success or failure of the scale inhibitor squeeze treatments. Previous studies have confirmed that interaction between the inhibitor and the scale surface plays an important role in scale prevention and control. Although many studies have been carried out on inhibitor efficiency and inhibition mechanism, a comprehensive understanding of inhibitor-scale interaction is yet available and the adsorption behavior between inhibitor and scale surface requires further research. Thereupon, this study presents performance evaluation and computational study of three inhibitors, including EDTMPS, DTPMP, and DTPA-5Na based on the scaling prediction result of the Huaqing oilfield. It was found that BaSO4 was the main type of scaling and the antiscaling performance of the three inhibitors was experimentally displayed as DTPA-5Na > DTMP > EDTMPS at the concentration from 40 mg/L to 120 mg/L. SEM micrographs of BaSO4 surfaces in the absence and presence of inhibitors at the concentration of 80 mg/L showed that the inhibitors obviously influenced the process of crystal growth of BaSO4 by lattice distortion and chelate effect. In addition, density functional theory (DFT) calculations unraveled that adsorption capacity of inhibitors interacting with three surfaces of BaSO4 increased in the order of DTPA-5Na > EDTMPS > DTPMP. DPTA-5Na was likely to be chemisorbed on the surfaces of BaSO4 while DTPMP and EDTMPS tended to be adsorbed on (210) and (001) surfaces of BaSO4 by chemical and physical effect, respectively. Calculation of difference charges and DOS analysis indicated that DTPA-5Na interacted with BaSO4 by combining atoms of oxygen and sodium to form new chemical bonds while EDTMPS and DTPMP interacted with BaSO4 by combining hydrogen and oxygen atoms to form physical bonds. The research results can provide a better understanding of the interaction between inhibitors and scale surfaces and can also lay scientific foundation for barite scale prevention and further development of inhibitors.